A new bilinear model for fatigue crack growth evaluation. (December 2022) - Zhuang, Bin-Bin; Liu, Yu-Xin; Du, Yan-Nan; Zhu, Ming-Liang; Xuan, Fu-Zhen
Abstract: Comparisons were made among the evaluation models of fatigue crack growth in various codes, standards, and guidelines, to illustrate the significance of transition point in accuracy. A new bilinear model was established with transition point and fatigue threshold fully considered, and was found more accurate than existing codes and standards for evaluation of fatigue crack growth behavior in both Paris and near-threshold regimes. Highlights: Conservativeness in existing codes and standards for fatigue crack growth assessment was compared. Transition point in fatigue crack growth was found significant in assessment accuracy. A new bilinear model for fatigue crack growth evaluation was developed.